PENERAPAN METODE REGRESI POLINOMIAL ORDE n PADA PENGEMBANGAN APLIKASI INVENTORY (STUDI KASUS PT. LANDIPO NIAGA RAYA) - Fitria Rihin Uyun; La Ode Muh. Golok Jaya; Natalis Ransi (semanTIK, 2019)
Inventory or inventory management system is one of the problems often faced by the distributor company. Processing and analyzing data on the sale of goods at the company is very important to get an overview and information about inventory data in the coming period by using sales data in the previous period, then an application or system is made with the Data Mining field with one of its predictions with using the Polynomial Regression method. This system predicts by selecting products, orders and periods with prediction results of 324,076 for Indomie Goreng Spesial Jumbo products. After making a prediction, a forecasting test is carried out by calculating the error value and relative errors with the result of error value = 2,595 and relative error = 1.82%.Keywords— Forecasting, Polynomial Regression, InventoryDOI : 10.5281/zenodo.3255112